Integrating Hybrid Sharia Contracts in Letter of Credit (L/C) Transactions for Export and Import in Islamic Banking in Indonesia - Sumanti, Eva; Al-Rasyid, Camelia Sofwan; Pitriani, Pitriani; Nurjaman, Muhamad Izazi; Alghani, Raid (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to analyze the application of the hybrid contracts concept in the Sharia export and import of L/C products in Indonesia to contribute to developing a practical or theoretical framework in Sharia banking. This article is a juridical-normative study using qualitative data from a literature study. Primary data comes from several DSN-MUI Fatwas related to L/C products, plus secondary data from a review of other reading materials relevant to the research topic. The data analysis techniques used are condensation, data presentation, and conclusion. This study found that the concept of hybrid contracts in sharia import and export L/C products has changed the status of L/C products, which were initially dominant service products with a single contract (wakālah bi al-ujrah) into various hybrid contract schemes with status as financing products. One of the hybrid contract schemes that are widely used is the murābahah bi al-wakālah contract, where the bank (issuing/advising bank) also provides funds in the form of purchasing imported goods, which are then resold to the importer or representing the sale of imported goods to the exporter.